2020
DOI: 10.1590/1678-4499.20190321
|View full text |Cite
|
Sign up to set email alerts
|

Budbreak induction in kiwifruit vines cultivated in an organic system by the biological method of single node cutting

Abstract: Kiwifruit vines are an alternative approach to diversify Brazilian fruit farming because of the low supply and increase in the demand for their fruits. Hydrogenated cyanamide, which is the most common rest-breaking agent, is highly toxic and its use is not allowed in organic production systems. This study aimed at evaluating the efficiency of alternative rest-breaking agents in kiwifruit vines by using the biological method of single node cutting. Twigs of the cultivar Bruno were collected in an organic orchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The modification of the ATS of a single cultivar over the two years depended on the quantity, quality, and duration of accumulated chilling hours, which varied for each cycle. This observation corroborates the findings of Santos et al (2020), who reported that changes in the accumulation of chilling hours, mainly due to insufficient chilling, can cause uneven and less intense sprouting. According to Carvalho and Biasi (2012), a reduction in the average sprouting time affects dormancy breaking.…”
Section: Discussionsupporting
confidence: 92%
“…The modification of the ATS of a single cultivar over the two years depended on the quantity, quality, and duration of accumulated chilling hours, which varied for each cycle. This observation corroborates the findings of Santos et al (2020), who reported that changes in the accumulation of chilling hours, mainly due to insufficient chilling, can cause uneven and less intense sprouting. According to Carvalho and Biasi (2012), a reduction in the average sprouting time affects dormancy breaking.…”
Section: Discussionsupporting
confidence: 92%
“…The recent advancement in organic farming has increased the demand for dormancy breaking organic compounds as safe alternatives for the chemical ones. Garlic (Allium sativum L.) extract is considered as one of the most effective organic compounds for dormancy breaking [67][68][69]. The application of garlic extract either alone (5-10%) or combined with mineral oil (2-4%) was highly effective in dormancy breaking of grape, apple, and kiwifruit [67][68][69].…”
Section: Dormancy Breaking Organic Compoundsmentioning
confidence: 99%
“…The application of fresh garlic extract, garlic oil, or di-allyl-sulfide stimulated dormancy breaking in grapevine without causing phytotoxicity in seedlings [68]. Garlic extract is rich in sulfur molecules, which produce cysteine as a result of reduced sulfur [69]. Cysteine metabolism leads to glutathione, which detoxifies ROS and free radicals.…”
Section: Dormancy Breaking Organic Compoundsmentioning
confidence: 99%